Reproducibility of physical performance during small- and large-sided games in elite soccer in short period: Practical applications and limits - Dellal, A.; Chamari, K.; Payet, F.; Djaoui, L.; Wong, D. P. (Journal of Novel Physiotherapies, 2016)
The aim of the present study was to examine the reproducibility of the physical activity during different sided games in elite soccer players during different training sessions. Twenty elite soccer players belonging to a French first league team (age: 24.3 ± 3.2 years; height: 178.1 ± 4.2 cm; body mass: 76.9 ± 4.3 kg) participated in different small and large-sided games (SSG: i.e. 5 vs. 5, 6 vs. 6, 7 vs. 7; and LSG: i.e. 8 vs. 8, 9 vs. 9 and 10 vs. 10 with and without goalkeepers) repeated at 2 different sessions within a competitive season. Peak speed reached (Vmax), heart rate (HR) responses and the total distance covered (TDC) at walking (0-6 km.h-1), very-light (>6-10 km.h-1), light (>10-16 km.h-1), moderate (>16-23 km.h-1), and high (>23 km.h-1) intensities were measured and analyzed using global positional system (GPS) during all SSG and LSG. No statistical significant differences of Vmax, HR response, TDC, and TDC at high and moderate intensities for all sided games played between 2 different sessions were found. Moreover, the inter-individual coefficients of variation of HR during all SSG were lower than 8.6% with no statistical significant differences when SSG and LSG were repeated at 2 different sessions. In conclusion, the physical performance and especially the high intensities activities of elite soccer players present good reproducibility when different types of SSG were applied in 2 different sessions in the same period, even if the rules and formats were being manipulated allowing coaches to use it with a target time-motion characteristic and an equivalent workload week after week.